What I Do Has to Be Great (Video) - Eichhorn, Kelsey (Cuizine)

(untitled) (McGill University Library, 2010)
A short documentary film that chronicles the life journey of Vermont dairy farmer and cheese maker John Putnam. The film explores a life-altering choice that is ultimately pitted against the sometimes-overbearing weight of societal expectation. Shot on location in rural Vermont.